2014
DOI: 10.1007/s00267-014-0349-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Canonical Correlation Analysis to Identify Environmental Attitude Groups: Considerations for National Forest Planning in the Southwestern U.S.

Abstract: As public land management agencies pursue region-specific resource management plans, with meaningful consideration of public attitudes and values, there is a need to characterize the complex mix of environmental attitudes in a diverse population. The contribution of this investigation is to make use of a unique household, mail/internet survey data set collected in 2007 in the Southwestern United States (Region 3 of the U.S. Forest Service). With over 5,800 survey responses to a set of 25 Public Land Value stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Although there is no general rule as regard the selection of the size of coefficient that are interpretable compared to factor analysis, but based on previous studies, the present study also reported only canonical variates whose absolute value is greater than 0.20 as cut-off point (Prera et al 2014). The results in Tables 5 and 6 are presented according to Dattalo (2014) for easy interpretation.…”
Section: The Relationship Between Personal Values and Consumption Valuesmentioning
confidence: 87%
See 1 more Smart Citation
“…Although there is no general rule as regard the selection of the size of coefficient that are interpretable compared to factor analysis, but based on previous studies, the present study also reported only canonical variates whose absolute value is greater than 0.20 as cut-off point (Prera et al 2014). The results in Tables 5 and 6 are presented according to Dattalo (2014) for easy interpretation.…”
Section: The Relationship Between Personal Values and Consumption Valuesmentioning
confidence: 87%
“…CCA is found to be commonly used in social and behavioral sciences and has been used by many researchers (Prera, et al 2014;Andleeb, 2016;Suchanek and Kralova, 2018). Several advantages are associated with CCA over others statistical tools.…”
Section: Canonical Correlation Analysis (Cca)mentioning
confidence: 99%